Dentigerous cyst involving mandibular second permanent molar: A case report - Kale, Sandeep; Shetty, Subraj; Pereira, Treville; Gotmare, Swati (Indian Journal of Case Reports, 2018)
Dentigerous cyst is the most common developmental odontogenic cyst, frequently noted as an incidental finding on radiographs. It commonly affects the permanent mandibular third molars and maxillary canines. We present a case of a dentigerous cyst involving an impacted mandibular second molar in a 21-year-old female.